Penerapan Prinsip Ekonomi Hijau dalam Pengembangan Pertanian Pedesaan dalam Perspektif Ekonomi Islam: (Studi Kasus Desa Mattoanging) - Nurfasira Nurfasira; Andi Ika Fahrika; Shadriyah Shadriyah (Universitas 45 Surabaya, 2025)
This study aims to analyze the implementation, suitability, benefits and constraints of green economic principles in the development of rural agriculture from an Islamic economic perspective in Mattoanging Village, Tellu Siattinge District. The research method used is a qualitative approach through an interview method involving Farmers, Mattoanging Village Officials, and the Agriculture Service. The implementation of green economic principles in agriculture in Mattoanging Village shows progress in maintaining environmental sustainability, improving economic welfare, and creating social balance. Practices such as crop rotation, use of organic fertilizers, and efficient agricultural technology support environmental impact reduction and increased healthier yields. However, challenges such as dependence on chemicals and high costs of organic fertilizers are still faced. This approach reflects the principles of Islamic economics which emphasize the balance between resource utilization and responsibility towards nature as a mandate from Allah SWT. Social justice practices, such as solidarity-based harvest distribution and fair wages, reflect sharia values ​​that prioritize equal distribution of sustenance and blessings. The values ​​of sustainability and welfare of the people in Islamic economics provide a spiritual foundation for the transition to a more environmentally friendly agricultural system. Intensive educational support and sharia-based policies are needed to accelerate this transformation. This study confirms that the synergy between the green economy and Islamic values ​​can create a sustainable, fair and blessed agricultural system.